Fostering Community Ownership for Sustainable Social Innovations in Pastoral and Agro-Pastoral Regions - Mulye Tadesse; Tafesse Matewos; Samuel Jilo Dira; Fekadu Israel Alambo; Tenaw Fentaw Dessie (Challenges)
Social innovation has emerged as a prominent strategy in development practice, attracting substantial scholarly attention. In Ethiopia’s pastoral and agro-pastoral areas, characterized by vulnerability and persistent development challenges, non-governmental organizations have begun implementing social innovations as alternatives to traditional interventions. However, the empirical understanding of the uptake of these innovations and the degree to which communities perceive ownership is limited. This study aims to investigate the adoption patterns of social innovations and evaluate community ownership of these innovations towards sustainability in specific Ethiopian contexts. Methods included partial participant observation, 12 case studies, 33 key informant interviews, and a sample survey of 392 respondents. The findings indicate that the average age of respondents is approximately 41 years old, with the youngest being 15 and the oldest being 94. Descriptive and inferential statistics showed that social innovations improved the management of the water system in Meda Wollabu and the enhanced goat market in Dasenech, with a developed sense of ownership benefitting and improving communities’ livelihood and sustainable development. The study concludes that developed sense of community ownership effective information dissemination, relative advantage and participation in training, highlighting the importance of tailored social innovation strategies that enhance community resilience and sustainability.